Hiring ethical hackers: the search for the right kinds of skills. Issue 2 (February 2017) - Mansfield-Devine, Steve
Abstract : We are constantly told that the UK and other countries are suffering from a serious lack of information security skills. That's almost certainly true when it comes to meeting the day-to-day operational security skills of organisations. But in one specific area – ethical hacking, or penetration testing – it's not so much an issue of quantity as quality. As Lawrence Munro, EMEA senior director for the SpiderLabs team at Trustwave, explains, it's getting people with the right kind of skills and attitudes that is most important.